Deep brain stimulation and complementary practices as a treatment of Parkinson’s disease - Righi da Silva, Larissa Pereira; Da Silva, Francielle Dutra; de Oliveira, Lara Barbosa; Zamberlan, Claudia (Disciplinarum Scientia | Saúde, 2024)
The objective of this study was to compare the effectiveness of two forms of treatment for Parkinson’s disease: Deep Brain Stimulation and Integrative and Complementary Practices. To this end, an integrative review of the literature was carried out with the following guiding question: “Deep brain stimulation is more effective in treating Parkinson’s disease when compared to Integrative and Complementary Practices. After comparison, it was identified that Deep Brain Stimulation is not more effective than Integrative and Complementary Practices, due to the possibility of having an adverse effect after surgery, progressing the symptoms of Parkinson’s Disease, while Integrative Practices do not have harmful effects when complementary to drug treatment. The need for more studies on Deep Brain Stimulation and Integrative and Complementary Practices as a treatment for Parkinson’s Disease was identified.